(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2024)
Supply chain management plays a role in ensuring the availability of raw materials from suppliers to the final product reaching consumers. Kelompok Ternak Mandiri Sejahtera (KTMS) is a cooperative that acts as a link between farmers and dairy processing consumers. However, research on the application of the supply chain concept at KTMS has not yet been explored. One commonly used approach to analyze supply chain conditions is the Food Supply Chain Network (FSCN). Therefore, the aim of this study is to analyze the fresh milk supply chain conditions at KTMS using the FSCN approach to comprehensively understand the supply chain conditions. The research was conducted at the Kelompok Ternak Mandiri Sejahtera (KTMS) from June to July 2024. The method used was qualitative descriptive with observations and interviews using questionnaires relevant to the Food Supply Chain Network (FSCN) framework with 17 respondents. The results of the study indicate that the fresh milk supply chain conditions at Kelompok Ternak Mandiri Sejahtera (KTMS), based on the Food Supply Chain Network framework approach, have been running smoothly, although transportation resources and technology resources remain weaknesses for both the farmers and KTMS.